2017
DOI: 10.3390/molecules22081377
|View full text |Cite
|
Sign up to set email alerts
|

Germination under Moderate Salinity Increases Phenolic Content and Antioxidant Activity in Rapeseed (Brassica napus var oleifera Del.) Sprouts

Abstract: The use of sprouts in the human diet is becoming more and more widespread because they are tasty and high in bioactive compounds and antioxidants, with related health benefits. In this work, we sprouted rapeseed under increasing salinity to investigate the effect on free and bound total phenolics (TP), non-flavonoids (NF), tannins (TAN), phenolic acids (PAs), and antioxidant activity. Seeds were incubated at 0, 25, 50, 100, 200 mM NaCl until early or late sprout stage, i.e., before or after cotyledon expansion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…In particular, dietary intake of free phenolics may be more rapidly absorbed during digestion and released in the body, inhibiting oxidation of low-density lipoprotein (LDL) cholesterol and liposomes, while bound forms may have chemopreventiveactivity against colon cancer [19]. However, it is worth noting that in other sprouts of herbaceous species, it has been found that the antioxidant activity of bound phenolics is lower than that of free phenolics [20,21]. For this reason, due to the nutritional relevance and effectiveness of free PAs, in this experiment, we detected only the free fraction of PAs and we cannot say whether VA was turned to the bound form or converted to other compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, dietary intake of free phenolics may be more rapidly absorbed during digestion and released in the body, inhibiting oxidation of low-density lipoprotein (LDL) cholesterol and liposomes, while bound forms may have chemopreventiveactivity against colon cancer [19]. However, it is worth noting that in other sprouts of herbaceous species, it has been found that the antioxidant activity of bound phenolics is lower than that of free phenolics [20,21]. For this reason, due to the nutritional relevance and effectiveness of free PAs, in this experiment, we detected only the free fraction of PAs and we cannot say whether VA was turned to the bound form or converted to other compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids represent the main group of polyphenols, with a wide array of biological roles, including lipid peroxidation inhibition [97][98][99]. Salt-induced increases in antioxidant phenolic levels have been reported in different plant species [100,101]. In S. vulgaris, a significant increase in total phenolic compounds was observed only in populations 1 (Mog) and 3 (Serp.…”
Section: Discussionmentioning
confidence: 99%
“…Salt tolerance is frequently studied by adding NaCl to the growth medium of plant in order to induce the salt stress [61]. The tolerance of water spinach seeds towards salinity was studied using different level NaCl solution as shown in Table 3.…”
Section: Effect Of Salinity On Salt Tolerancementioning
confidence: 99%